Baking Soda (Sodium Bicarbonate) As An Alternative To Lithium Carbonate Blueing Agent In Hematoxylin-Eosin Staining - Burhanuddin Burhanuddin; Malik Abil Fadli; Neiny Prisy Foekh; Ayu Putri Utami (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Hematoxylin-eosin staining is a crucial technique used in histopathology to differentiate tissue components. One of the steps in this staining is changing the color of the nucleus, which was previously reddish due to the acid solution, to bluish; this step is known as blueing. The bluing agent, lithium carbonate, is commonly used in laboratories but has side effects and low availability. Sodium bicarbonate, also known as baking soda, can be used as an alternative due to its optimal pH, lower toxicity, and availability. This study aims to find out whether baking soda is as effective as lithium carbonate when used as a blueing agent for hematoxylin-eosin staining. The study design used was a true experimental post-test only control group design with a sample size of 32 preparations. Results of preparations using baking soda microscopically had good color uniformity, the nucleus was visible, the cytoplasm was clear, so the boundaries between cells were visible, and no cell lysis was found. In percentage terms, 14 preparations received a score of two (87.5%), two preparations received a score of three (12.5%), followed by a P value of 0.051 after carrying out the Fisher's exact test in bivariate analysis. Based on the results, baking soda is as effective as lithium carbonate, so it can be used as an alternative to bluing agent of hematoxylin-eosin staining.